Vitamin D and prostate cancer - Feldman, David (Henry Stewart Talks, 2007)
Vitamin D actions: classical view and expanded view, Vitamin D metabolic pathways, Vitamin D and cancers, Vitamin D-deficiency hypothesis, Sunlight, vitamin D and prostate cancer risk, Importance of local production of calcitriol, Importance of 24-hydroxylase activity level, Differential sensitivity to antiproliferative actions of calcitriol, Inhibition of 24-hydroxylase activity by liarozole, Anti-cancer mechanisms, Calcitriol and inflammation, COX-2 actions and prostate cancer, Inflammatory mechanisms in carcinogenesis, COX-2 and PG induction of cancer, Three calcitriol actions to inhibit PG activity, Potential synergy of calcitriol with NSAIDs, Results of vitamin D therapy in in vivo trials of prostate cancer, Calcitriol and naproxen, Genetic mouse model of PIN-HG-PIN, High dose intermittent calcitriol plus docetaxol